Literary unity in the Coptic cycle of Arianus - Lilia Frangulian (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
The article is devoted to the Coptic cycle gathered around the name of the persecutor Arianus and consisting of three diff erent martyrdoms. They are extant in one MS. The texts in it are arranged in a chronological order following the logic of the narrative. These three texts make up a literary unity occurring only in the Coptic tradition. All martyrdoms are united, fi rstly, by a single background of events, i.e. the city of Antinopolis, and, secondly, by the fi gure of the persecutor Arianus. In the fi rst two texts, this character is the antagonist, and in the third it is the protagonist. The research shows that the prototype of Arianus is Apostle Paul. An allegory to the New Testament story of Paul can be found in the general narrative of the cycle, where each of the three texts sequentially represents the prologue, the set and the denouement. This cycle has never been studied from a philological point of view, but it is this analysis that makes it possible to determine the literary and non-literary methods used by the author of the cycle in order to integrate the three texts.